2017
DOI: 10.1111/1755-5922.12268
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin responsiveness changes in obese patients following bariatric surgery

Abstract: Aspirin-induced platelet inhibition may be more potent following bariatric surgery. The mechanisms behind this improvement require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Although it was a small study, the authors conclude that patients were not at increased bleeding risk when using low-dose ASA 121 weeks after surgery whereas in controls, the IC50 level of ticagrelor was 14.5 nM. This suggests that bariatric surgery improves the ticagrelor pharmacodynamic response that was blunted by obesity, which is also showed in the study of Norgard described above 115 .…”
Section: Platelet Aggregation Inhibitorsmentioning
confidence: 62%
See 3 more Smart Citations
“…Although it was a small study, the authors conclude that patients were not at increased bleeding risk when using low-dose ASA 121 weeks after surgery whereas in controls, the IC50 level of ticagrelor was 14.5 nM. This suggests that bariatric surgery improves the ticagrelor pharmacodynamic response that was blunted by obesity, which is also showed in the study of Norgard described above 115 .…”
Section: Platelet Aggregation Inhibitorsmentioning
confidence: 62%
“…After surgery, the platelet reactivity was significantly reduced (432 ± 143 vs. 469 ± 60 ARU p=0.03), which was also seen in RYGB patients who did not use ASA (602 ± 59 vs. 531 ± 78 ARU p=0.035). This shows that the reduced reactivity after surgery compared to preoperative values may not be solely related to ASA 115 .…”
Section: Platelet Aggregation Inhibitorsmentioning
confidence: 77%
See 2 more Smart Citations
“…Subgroup analyses of large trials of antithrombotic drugs are based on a few participants with class ≥2 obesity, and outcome trials specifically recruiting moderately to severely obese patients are lacking. Uncontrolled, small studies with a pre‐post design showed, that in subjects with class ≥3 obesity undergoing bariatric surgery, platelet responsiveness to aspirin (assessed in whole blood with the Verify Now assay, Accumetrics, San Diego, CA) improved after bariatric surgery and weight loss . Consistently, plasma levels of salicylic acid have been reported to increase after bariatric surgery and weight loss …”
Section: Introductionmentioning
confidence: 92%